PROFITABILITY, COMPANY SIZE, DIVIDENDS, AND CAPITAL STRUCTURE EFFECTS ON COMPANY’S VALUE - Wongso, Karin Oxana; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2023)
The main purpose of this research is to obtain evidence or answers referring to the effect of profitability, company size, dividends, and capital structure on the value of consumer non-cyclical manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research used purposive sampling technique. This research used 24 consumer non-cyclical manufacturing companies with a total of 72 samples during the period. The result of this research was obtained by using application which was called Eviews-12 with regression analysis technique. By using the technique and application, the result show that profitability and company size have a significant effect on company’s value. However, dividends and structure effects do not have a significant effect on company’s value.